Improvement of Immune and Hematopoietic Functions by Litsea japonica Fruit Extract in Cyclophosphamide-Treated BALB/c Mice - Seon Yeong Ji; EunJin Bang; Hyun Hwangbo; Min Yeong Kim; Da Hye Kim; Young Tae Koo; Jin Soo Kim; Ki Won Lee; Sun Young Park; Chan-Young Kwon; Hyesook Lee; Gi-Young Kim; et al. (Applied Sciences, 2022)
Loss of immunity is an important cause in the pathology of infectious disease. This study investigates the effect of Litsea japonica fruit extract (LJFE) as a potential functional food on immunity and hematopoietic function in immunosuppressed BALB/c mice. Immunity-stimulating activity was observed in mice supplemented with LJFE at low (25 mg/kg), medium (50 mg/kg), and high (100 mg/kg) dosage for seven days after administration of cyclophosphamide. LJFE treatment significantly improved spleen injury score (p < 0.001) and body weight (p < 0.02) by approximately two-fold with a high dosage of LJFE (100 mg/kg). Spleen-derived lymphocyte analysis demonstrated that the numbers of clusters of differentiation (CD)4+ and CD8+ T-cells were notably increased by approximately two-fold (p < 0.001) with a high dosage of LJFE (100 mg/kg). In mouse splenocytes differentiated into T- and B-lymphocytes, LJFE significantly induced proliferation up to approximately 90% of control for T- (p < 0.001) and B-lymphocytes (p < 0.01) with a high dosage of LJFE (100 mg/kg). Furthermore, LJFE significantly recovered the numbers of white blood cells, red blood cells, and platelets. Enzyme-linked immunosorbent assay revealed that serum levels of immune-related cytokines, such as tumor necrosis factor-α, interleukin (IL)-1β, IL-6, IL-2, and interferon (IFN)-γ, were notably Increased. In addition, serum levels of immunoglobulin (Ig) A, IgM, and IgG were restored by LJFE treatment. This study provides a reference to use L. japonica as a functional food ingredient to improve immunity and hematological function in humans.